2018
DOI: 10.1159/000489850
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Radioiodine Ablation in Patients with Low-Risk Differentiated Thyroid Cancer

Abstract: Aim: Based on the response criteria of the 2015 American Thyroid Associations guidelines, our objectives were to ­determine the response rate when using a low dose of ­131-I GBq in patients with low-risk differentiated thyroid cancer (LRDTC) and the influence of clinical and analytical variables on the prediction of complete response. Methods: We performed a multicentre and longitudinal study, including patients who were operated for LRDTC and who underwent radioiodine remnant ablation with a low-dose of 131-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…The main difference of our study to HiLo was anti-TgAb consideration that was not described in this clinical trial, and with ESTIMABL1 the difference was the inclusion of intermediate-risk tumours. Nevertheless, the rate of excellent response in the low-dose group was 78.9%, and this result is comparable to previous studies [8,9,11,14,15].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The main difference of our study to HiLo was anti-TgAb consideration that was not described in this clinical trial, and with ESTIMABL1 the difference was the inclusion of intermediate-risk tumours. Nevertheless, the rate of excellent response in the low-dose group was 78.9%, and this result is comparable to previous studies [8,9,11,14,15].…”
Section: Discussionsupporting
confidence: 90%
“…In the HiLo study, they compared low-risk and intermediate-risk tumour recurrence rates with low (<100 mCi) and high doses (≥100 mCi) of RAI, showing a noninferior result (1-2% risk of recurrence at 5 years in both groups) [8]. Other authors, such as Ghachem [9], Schlumberger [14], Qi [15] or Jiménez-Londoño [11], have reported similar results in observational studies, concluding that low doses were noninferior to high doses in patients with low-risk thyroid cancer. In our study, we observed a higher rate of indeterminate responses in the group treated with low doses of RAI and a higher rate of excellent and incomplete biochemical responses in the group of high-dose ablation, with statistical significance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, treatment of DTC with 131 I is still an open issue because recommendations of experts are based only on data interpretation of observational retrospective studies. The results of the prospective trials are pending, and the use of 131 I is justified in high-risk, intermediate-risk, and low-risk patients [71,72] according to the guidelines of the American and British Thyroid Association, European and American Societies of Nuclear Medicine, the European Consensus Group, and the latest edition of National Comprehensive Cancer Network (NCCN) [71,73].…”
Section: Physical Factorsmentioning
confidence: 99%
“…8 Additionally, some authors have concluded that a low dose of radioiodine is as effective as a high dose of radioiodine for ablation of the thyroid remnant after total thyroidectomy for low-risk DTC. [33][34][35] Several factors are associated with unsuccessful RAI ablation, but in most studies, only lymph node recurrence was a significant factor. 36 In this research, in addition to lymph node recurrence, we found persistent positive Tg value and some false positive I-131 imaging, like thyroglossal duct cyst and thymoma uptaking I-131, all led to multiple RAI.…”
Section: Discussionmentioning
confidence: 99%